An Explorative Study of The Entrepreneurial Ecosystem in Sharjah - AlNaqbi, Nour Nasir (2025)
A Master of Business Administration (MBA) thesis by Nour Nasir AlNaqbi entitled, “An Explorative Study of The Entrepreneurial Ecosystem in Sharjah”, submitted in May 2025. Thesis advisor is Dr. Rodrigo Basco. Soft copy is available (Thesis, Approval Signatures, Completion Certificate, and AUS Archives Consent Form).